Forecasting football injuries by combining screening, monitoring and machine learning - Hecksteden, A.; Schmartz, G. P.; Egyptien, Y.; Aus der Fünten, K.; Keller, A.; Meyer, T. (Science and Medicine in Football, 2023)
Identifying players or circumstances associated with an increased risk of injury is fundamental for successful risk management in football. So far, time-constant and volatile risk factors are generally considered separately in either a screening (constant) or a monitoring (volatile) approach each resulting in a restricted set of explanatory variables. Consequently, improvements in predictive accuracy may be expected when screening and monitoring data are combined, especially when analysed with current machine learning (ML) techniques.